Persepsi Guru Terhadap Penggunaan Game Edukasi dalam Meningkatkan Keterlibatan dan Pemahaman Siswa di Sekolah Dasar - Amikratunnisyah, Amikratunnisyah; Qahfi, Bung Ashabul (FONDASI: Jurnal Pendidikan Dasar, 2025)
Abstract: This research examines teachers' perceptions of the use of educational games in enhancing student engagement and understanding in elementary schools through a literature review method. The results indicate that educational games have significant potential to promote student engagement, increase intrinsic motivation, and deepen conceptual understanding, especially in complex subjects. However, the main challenge lies in selecting games that align with the curriculum and the technological readiness of schools. Structured training for teachers is necessary to improve their skills in integrating educational games. Additionally, collaboration between teachers and game developers, as well as support from educational policies, is crucial for successful implementation. This study recommends further research on the long-term impact of using educational games on students' academic performance and social skill development.